KHADIJAH AL KUBRA: Peran Perempuan Agung dalam Kehidupan - Marwazi Marwazi (Center for Gender and Children Studies, Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) UIN Sultan Thaha Saifuddin Jambi, 2020)
This descriptive writing highlights two dominant roles play by Siti Kahdijah al-Kubra, the wife of the Prophet Muhammad saw. Her glorious roles are both in spiritual and material. The first one is proven when she took part side by side by the prophet in his royalty and sicience action supporting the strunggle of the Prophet and, the latter; she is willing to sacrifice her wealth to support her beloved husband in peraching the newly born religion, Islam. Khadijah, now is the exemplary model for Islamic women in the world in all action the do.